Intramuscular Neck hemangioma - A Case Report (Bangladesh Journal of Nuclear Medicine, 2022)
Intramuscular hemangiomas are rare neoplasms of blood vessel origin located inside muscles, which may not be clinically apparent at presentation. We present one such interesting case which was deceiving enough to remain unnoticed on initial short clinical examination and produced a misleading cytological diagnosis up front. High resolution ultrasound gave a clue to the diagnosis of the tumor. More specific radio-labelled RBC scan confirmed its presence, while fusion imaging pin-pointed its location.Bangladesh J. Nuclear Med. 24(1&2): 68-72, 2021